2016
DOI: 10.1007/s13679-016-0219-6
|View full text |Cite
|
Sign up to set email alerts
|

Retail Environments as a Venue for Obesity Prevention

Abstract: Increasing attention has been given to the role of retail food environments in shaping dietary behavior and obesity risk. Studies have generally shown an association between living in a neighborhood with or in close proximity to certain types of food outlets and/or the availability of healthy food options and better dietary quality, higher fruit/vegetable intakes, and a lower risk of overweight, even after controlling for individual/family level characteristics. However, research in this area has yielded mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 101 publications
0
25
0
1
Order By: Relevance
“…28,29 Studies have generally shown an association between living in a neighborhood in close proximity to certain types of food outlets and the availability of healthy food options, dietary quality, dietary intake, and risk of overweight. 3033 However, there is a gap in understanding how sugar-sweetened beverage availability in various food environmental settings (home, school, neighborhoods) are linked with adolescent sugar-sweetened beverage consumption. 28,34,35 …”
Section: Discussionmentioning
confidence: 99%
“…28,29 Studies have generally shown an association between living in a neighborhood in close proximity to certain types of food outlets and the availability of healthy food options, dietary quality, dietary intake, and risk of overweight. 3033 However, there is a gap in understanding how sugar-sweetened beverage availability in various food environmental settings (home, school, neighborhoods) are linked with adolescent sugar-sweetened beverage consumption. 28,34,35 …”
Section: Discussionmentioning
confidence: 99%
“…29 A recent review by Minaker and colleagues 30 particularly highlights the lack of research on the consumer food environment in Canada, with only one paper that used measures of the consumer food environment to study the association between food environment and health outcomes. While store proximity and availability in one's neighbourhood have been linked with diet quality, studies have reported inconsistent results, 31 suggesting that physical accessibility alone might not be sufficient to explain dietary habits. The availability and affordability of the foods within those stores may be contributing to the association between food store access and food store choice, eating behaviours and health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Inagami et al 46 found in a study conducted in the Los Angeles area of California, USA, that BMI was higher (A) where persons frequented grocery stores located in more disadvantaged neighbourhoods, which usually have higher availability of relatively inexpensive, energy-dense foods and (B) among those who owned cars and travelled farther to their grocery stores. However, other studies reveal inconsistencies, with mixed findings across various neighbourhood food retail contexts which may be due to the heterogeneity in defining neighbourhoods using SES 47 48 and methodological limitations in measuring the inter-relatedness of neighbourhood residence, determinants of purchasing choices within and outside of the residential neighbourhood and issues such as dietary preferences. 49 In our study, PAL, motorised transport and diet were not adjusted for in the regression models.…”
Section: Discussionmentioning
confidence: 99%